From "higher law" to "sectarian scruples" - Hitchcock, James, 1938- (Hitchcock, James. Supreme Court and religion in American life, 2004)
School vouchers. The Pledge of Allegiance. The ban on government grants for theology students. The abundance of church and state issues brought before the Supreme Court in recent years underscores an incontrovertible truth in the American legal system: the relationship between the state and religion in this country is still fluid and changing. This, the second of two volumes by historian and legal scholar James Hitchcock, offers a complete analysis and interpretation of the Court's historical understanding of religion, explaining the revolutionary change that occurred in the 1940s. In.